Post-Traumatic Stress Disorder Among Sexually Abused Children: The Role Of Traumagenic Dynamics Model - Fatmawati, Fatmawati (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2016)
Sexual abuse is one of the most serious cases occurring in this present day, and the statistical trend generally classifies the children to be more vulnerable compared to other groups in the population, where the female children show the highest prevalence among others (Pérez-Fuentez et al., 2013; Stoltenborgh, van Ijzendoorn, Euser, & Bakernas-Kranenburg, 2011). The children who have been exposed to sexual abuse may increase their risk of developing psychological problems, such as: depression, eating problem, anxiety, psychosis, substance abuse, thoughts of suicide, etc (Makhija, 2014). Furthermore, some research findings mention that post-traumatic stress disorder (PTSD) is the most common mental health problem that occurs after sexual abuse and the symptoms arisen may have different effect for the children as the victims (Martinson et al., 2013). In order to comprehend this issue, Finkelhor and Browne (1988) has formulated a model called traumagenic dynamics model which comprehensively illustrates the trauma caused by childhood sexual abuse and describes it as long-term effects during the life span. As a way to investigate the trauma caused by sexual abuse, the model has conceptualized the four factors which are labelled as traumagenic dynamics, these include: traumatic sexualization, betrayal, powerlessness, and stigmatization or self-blame (Finkelhor & Browne, 1988).